B-Complex Alleles Immunity to Salmonella enteritidis in Chickens - Soliman, E.S.; Reddy, P.G.; Nimmanapelli, R.; Abouelhassan, E.M. (International Journal of Poultry Science, 2009)
Six experiments were conducted during which a total of 12 congenic lines homozygous for various B-complex alleles, were challenged by intraperitoneal injection with either of two isolates of Salmonella enteritidis. Because these B alleles were expressed on a common genetic background and mortality differences among lines were statistically significant in three of the six trials and morbidity (body weight) differences were significant in another trial; it is suggested that B-complex alleles affect the degree of immunity to these isolates. When all lines and trials were compared, line 342 (BC/BC) emerged as particularly resistant, whereas lines 253 (B18/B18) and 254 (B15/B15) were more susceptible. The remainders of the lines were of neutral (intermediate) susceptibility. Sex did not appear to influence the results of the challenge, but more resistance was observed with an increase in the age at inoculation. Although the mechanism that determined this resistance is unknown it was present as early as 3 d of age and it is suggested that complement proteins, which have a known role in protection from bacterial infections and are encoded by genes located within the B-complex, or acute phase proteins, may account for these observations.